Simulation study on RFID application to crossdocking operations - Lin, Jincong. (2009)
The rapid advancement and falling prices of RFID technology is gradually encouraging many companies within the supply chain to consider deployment. Its benefits in comparison to the prevalent barcode are opening up a myriad of possibilities envisioned to attaining operational efficiencies. In an era where product lifecycles and order lead times are ever decreasing, RFID seemed poised to be the solution.